In vitro silencing effect of chitosan nanoplexes containing siRNA expressing vector targeting VEGF in breast cancer cell lines - (:unkn) unknown (GOVI-VERLAG PHARMAZEUTISCHER VERLAG GMBH, 2010)
Small interferring RNA (siRNA) is a powerful tool for controlling cellular processes of gene silencing at post-transcriptional level due to its high sequence-specific inhibition efficiency. The aim of this study is to compare silencing effect of chitosan/shVEGF (shRNA-expressing plasmid DNA targeting vascular endothelial growth factor-A (VEGF-A)) nanoplexes between four different cell lines, two of which are MCF-7 and MDA-MB435 breast cancer cell lines. Nanoplexes were prepared using different concentrations. The morphological and physicochemical characterization were made and silencing activity of appropriate formulations were investigated in vitro. As a result of in vitro transfection studies made in different cell lines with nanoplexes in the different ratios, the highest gene inhibition (60%) was measured in MCF-7 after transfection while the lowest gene inhibition (29%) was observed in MDA-MB435. This work suggests that RNA interference has potential to be applied to delivery system studies and to the angiogenesis treatment.
Keywords: RNA INTERFERENCE; GRAFT-POLYETHYLENIMINE; DNA NANOPARTICLES; CATIONIC LIPIDS; GENE DELIVERY; TUMOR-GROWTH; ANGIOGENESIS; TRANSFECTION; CARRIER; MODEL